Maternal phthalate exposure during pregnancy and testis function of young adult sons - Henriksen Louise S; Frederiksen Hanne; Jorgensen Niels; Juul Anders; Skakkebaek Niels E; Toppari Jorma; Petersen Jorgen H; Main Katharina M (ELSEVIER, 2025)
Background: Phthalate exposure during fetal life may disrupt testicular development. Congruent with this, studies have found shorter anogenital distance, reduced penile size and altered hormone levels in infant boys whose mothers were exposed to higher levels of some phthalates during pregnancy. Few studies have explored if such adverse effects persist in adulthood. Thus, we aimed to explore if there is an association between fetal phthalate exposure and markers of testicular function in young adult men.
Methods: In a longitudinal mother-child cohort from Copenhagen, Denmark, we examined 100 young men whose mothers during pregnancy had serum drawn and analyzed for 34 phthalate metabolites. Examinations of the young men took place at 18-20 years of age and included measurements of adult markers of testicular function (reproductive hormones, penile size, anogenital distance (AGD), testis volume, semen quality) and growth factors. Associations between maternal serum concentrations of phthalate metabolites and reproductive measures in the young men were tested using multiple linear regression.
Results: Most consistently, higher maternal phthalate exposure was associated with higher luteinizing hormone (LH) but unchanged testosterone in adult sons. Congruently, higher maternal exposure was associated with lower total and free testosterone/LH ratios in adult sons. For example, twice as high maternal MiNP was associated with a 7.9 % (95 % CI 1.6-13.8) lower free testosterone/LH ratio. There was no consistent pattern of associations between the different phthalate metabolites and other reproductive hormones, clinical outcomes, or semen quality. None of the tested associations was significant after multiplicity adjustment.
Conclusions: In this exploratory study, higher maternal exposure to some phthalates was associated with impaired testicular Leydig cell function evidenced by a lower total and free testosterone/LH ratio in adult sons. This unique 18-20-year follow-up study raises concern and suggests that exposure of pregnant women to phthalates may have long-term effects on adult reproductive health in male offspring.